Factors Influencing the Choice of Agricultural Information Sources Among Banana Farmers in Chitwan District, Nepal - Mishra, Binayak Prakash; Singh, Om Prakash (Journal of Agriculture and Forestry University, 2025)
Agricultural information is essential to improve the farming practices in the developing countries like Nepal. However, the farming communities are still devoid of access to timely and accurate information making agriculture solely rely on traditional knowledge and practices. An investigation was carried out during 2021 in the Chitwan district of Nepal to identify the factors influencing the choice of agricultural information sources among banana farmers. To gather primary data, a household survey was carried out with 75 banana farmers using pretested semi structured questionnaire, followed by a Focus Group Discussion (FGD) and Key Informant Interview (KII) with selected individuals. Descriptive statistics and multivariate probit model were used to present the findings. Results revealed that gender, age, education, income, farm size and membership in farmer’s organization were statistically significant in influencing the choice of agricultural information sources. Hence, the study suggests that information providers should tailor their working mechanism through the specification of farming communities. Farming communities should no longer be treated as homogeneous group by the extension agencies in the flow of agricultural information.